PEAK HOUR AT SMALL AIRPORTS – A CASE STUDY FOR REGIONAL AIRPORTS UNDER CONCESSION IN BRAZIL - Lopes, Dario Rais (International Journal of Engineering Science Technologies, 2025)
This paper compares the different peak hour values (a reference for infrastructure planning) at regional airports under concession in Brazil. This assessment is based on the different criteria proposed by international entities, regulatory agencies and the concession contract itself. These criteria are applied to two regional airports under concession in the State of São Paulo. The main results indicate that the use of the criteria of the current regional airport concession contracts to calculate peak hour leads to an underestimation of airport facilities, which becomes worse as the airport's regular traffic decreases, leading to a service level much lower than expected at a concessioned airport.